PARTICIPATION OF INTESTINAL DIFFERENTIATION TRANSCRIPTION FACTOR CDX2 IN THE HISTOGENESIS OF THE GASTROINTESTINAL TRACT - Rekun, T.O.; Trofimenko, Yu.Yu.; Balynska, M.V.; Loboda, I.V. (World of Medicine and Biology, 2018)
The purpose of the present study was to explore expression and role of CDX2 in the differentiation of anterior and posterior parts of the gastrointestinal tract in the human embryos and fetuses in gestation age 4-38 weeks. The current study was carried out on 169 autopsied formalin-fixed human embryos and fetuses of gestational age 4–38 weeks of Caucasian ethnic origin. It was found that expression of CDX2 was negative in all cases as in esophageal so in gastric epithelium, despite its moderate expression in small and large intestine. This indicates that CDX2 is important transcription factor of development and differentiation of exactly intestinal epithelium. According to this view, immunohistochemical and functional experimental investigations point to appropriate CDX2 expression during the Barrett’s esophagus formation and on the contrary conditional removal of CDX2 in the intestine causes squamous metaplasia. Expression of intestinal differentiation transcription factor CDX2 was typical for epithelial differon of lower parts of the gastrointestinal tract and wasn’t noticed by us in the enterocytes nuclei of the esophagus and stomach.
Keywords: embryogenesis; transcription factor CDX2; gastroesophageal and intestinal epithelium; gastrointestinal tract